Exploring EFL Higher Education Learners’ Attitudes Toward Writing Skills Process - Samsul Amri (PANYONARA: Journal of English Education, 2022)
Learners' writing attitudes have been heavily debated as a research topic. The main objective of this current investigation is to explore the learners' attitudes towards the writing process and functions at the higher education level. It is designed as a quantitative approach, with the design as survey research. Thirty-five learners of the English Study Program of FKIP Universitas Islam Indragiri were chosen as the samples. The researcher utilized a questionnaire designed on a Likert scale in obtaining the data. Then the data was analyzed using descriptive statistical analysis, which included individual scores, percentages, mean scores, and attitude level. The findings indicate that the learners' attitudes toward the writing process and functions ranged in the mean score of 3.83, which was categorized as a positive attitude. Therefore, it can be inferred that they have good skills for writing because they have a positive attitude toward writing.